EDUCATION VALUES AND MORALITY OF THE MAIN CHARACTER IN “THE THEORY OF EVERYTHING” BY JAMES MARSH - Is Mariyani (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This research aims to analyze the values and character building in “The Theory of Everything,” to identify the morality of the main character of “The Theory of Everything” 3) the method of value formation, and 4) the implications of using this film in character building and morality in children. This research is done by using a descriptive qualitative method with a literature-based approach. This research uses content analysis, which analyzes the content of dialogue, scene, and character according to the value of character education and morality of the main character. Based on the result of research, it can be concluded that this film contains 1) the values and character building, such as religious, honesty, tolerance, hard work, creativity, independently, curiosity, nationalism, loving the country, respect for achievement, friendly or communicative, peaceful love, fond of reading, caring society dan responsibility. 2) the moral value of the main character, which is dominant, is as honest, independent, and hard work. 3) the method of value formation through dialogue and very inspirational scenes through the main characters; and 4) the implications of using this film in character building and morality in children is to build self-confidence and self-actualization.Keywords: character education; film analysis; moral values